PENGGUNAAN NaOCl DI SAMPEL SPUTUM PEMERIKSAAN BTA UNTUK MENINGKATKAN DERAJAT KEPOSITIFAN DIAGNOSTIK MIKROSKOPIK TUBERKULOSIS - Vector Stephen Dewangga; Andryaning Putri Puspitasari (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis bacteria is still a health problem in the world, including Indonesia. One way to diagnose this disease is by microscopic examination in the form of Acid Resistant Basil (BTA) staining by the Ziehl-Neelsen method using sputum specimens. This check in Indonesia is very often used because the material price is quite affordable and easy to get. Sodium hypochlorite is a disinfectant solution that can be beneficial as a sputum thinner. The purpose of this study was to analyze the degree of positivity of BTA coloring results with the use of NaOCl solution of 0.25%, 0.5% and 1%. The Research Design used in this descriptive descriptive research is Observational. The subject of this study was a suspected sputum sample of TB at Aisyiyah Klaten RSU on February 10, 2025 to February 24, 2025 with a total of 10 samples. From the results of the study obtained degrees of positivity of microscopic TB diagnostics between without use of NaOCl solutions compared with the use of NaOCL 0.25%, 0.5% and 1%. Conclusion: The use of Sodium Hypochlorite (NaOCl) in sputum samples has been shown to increase the degree of positivity of microscopic diagnostic tuberculosis. The number of positive samples increased from 6 samples in the group without NaOCl to 6 postive samples and 2 scanty samples in the group with NaOCl 1%. In addition, there was an increase in positivity score from +1 to +2 in 4 samples and from negative to scanty in 2 samples after the use of NaOCl of 1%. NaOCl concentration 1% is the best concentration capable of increasing the average value of the number of Mycobacterium tuberculosis cells. The average number of BTA cells increased from 809 cells in the group without NaOCl to 2,168 cells in the group with 1% NaOCl. This concentration also converts 2 samples that were initially negative into scanty. In addition, the addition of this bleach solution can also improve the clarity of the visibility of the microscope.